The Invention of Hebrew Prose: Literary Language and the Dilemmas of Mimesis, pt. 3, sect. 1 - Alter, Robert (University of Washington Press, 1987)
DIscussion of how the Hebrew literary language developed and how it is used to create a reality.
Realism Without Vernacular, pt. 1
Keywords: Hebrew fiction--History and criticism ; Mimesis in literature